Sosialisasi Gizi Seimbang Dalam Memilih Makanan Sehat di Sekolah Dasar Negeri Mandiro 2 - Agung Nugroho Puspito; Mohammad Ubaidillah; Rahma Nur Safitri; Elina Porwaning Sukma; Sella Sandra Aureliya; Rimadhini El-Syifani; Meutia Anjani Aprillia (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
Nutrition issues in primary school-age children are still a major concern, with many students not understanding the concept of balanced nutrition and often consuming unhealthy foods. The socialization activity regarding balanced nutrition and healthy food selection at Sekolah Dasar Negeri Mandiro 2 aims to increase students' knowledge about the importance of balanced nutritional intake and healthy food selection in supporting their growth and development. The methods used in this socialization are interactive lectures and interesting educational media, such as pictures and videos to explain the types of healthy foods. The results of this socialization are expected to provide students with a better understanding of healthy eating patterns and encourage them to apply balanced nutrition in their daily lives.